2015
DOI: 10.15637/jlecon.51
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Outdoor Activities on Life Satisfaction: An Application of Propensity Score Matching of a Case in Turkey

Abstract: A large part of this research focuses on life satisfaction changes depending on the multiple causal effect, but in recent years, the impact of life satisfaction on outdoor sports based on the theory of activity sports, has taken on a new dimension with research methods. This article briefly discusses not only some of the most common causal methods on observational data for comparative effectiveness research to implement propensity score matching, but also presents measurement of life satisfaction. Using the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
0
0
Order By: Relevance
“…Broadly, time spent outdoors engaging with nature has been positively associated with subjective well-being. Research has found that those who engaged in more outdoor activities tended to have higher life-satisfaction (Biedenweg, Scott, & Scott, 2017) controlling for income, leisure, education, and employment (Mert, Zurnaci, & Akgün, 2015). A recent meta-analysis (McMahan & Estes, 2015) found that across thirty-two samples, brief contact with natural environments increased positive affect and decreased negative affect.…”
Section: Nature and Well-beingmentioning
confidence: 99%
“…Broadly, time spent outdoors engaging with nature has been positively associated with subjective well-being. Research has found that those who engaged in more outdoor activities tended to have higher life-satisfaction (Biedenweg, Scott, & Scott, 2017) controlling for income, leisure, education, and employment (Mert, Zurnaci, & Akgün, 2015). A recent meta-analysis (McMahan & Estes, 2015) found that across thirty-two samples, brief contact with natural environments increased positive affect and decreased negative affect.…”
Section: Nature and Well-beingmentioning
confidence: 99%